Manajemen Kepemimpinan Pendidikan di Pesantren Berbasis Prinsip Progress of Change - Muhammad Madarik (Universitas Al-Qolam Malang, 2025)
Islamic boarding schools (pesantren) are currently facing a critical phase of structural transition, moving away from traditional, single-figure leadership centered around the Kiai toward a more professional, collective management model. This study aims to formulate a strategic planning model for pesantren leadership transition based on the Islamic principle of